Pembaharuan Inovasi dalam Budidaya Pisang serta Pajak Pertambahan Nilainya - Septanta, Rananda; Khuzaeni, Khuzaeni; Arslan, Rijal; Nurhasan, Yunus (Jurnal PKM Manajemen Bisnis, 2025)
The increasing need for sustainable food sources and economic empowerment in underprivileged communities has become a critical concern, especially in urban areas like South Tangerang. In response, a community service program titled "Training on Banana Cultivation and Optimization of Its Economic Value" was conducted at the Pondok Miri Orphanage Foundation. This initiative aimed to enhance the agricultural knowledge and entrepreneurial skills of 41 students from the orphanage by introducing banana cultivation techniques and strategies to maximize its economic potential. Held in April 2025, the activity was carried out by 10 lecturers from Pamulang University using a combination of methods, including material presentation, group discussions, and practical training in planting and marketing. The results indicated a significant improvement in participants’ understanding of sustainable farming practices and their ability to identify and leverage economic opportunities through banana-based products. This program not only fostered environmental awareness but also laid the groundwork for future micro-business development among the youth.